PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI PENGGUNAAN MEDIA SOSIAL DI KOTA SAMARINDA - Khairunnisah, Endi Dwi Saputra dan (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
The crime of defamation that often occurs in cyberspace is an act that attacks the good name. Offensive reputation is to convey words (words or a series of words / sentences) by accusing certain acts of being committed, and those aimed at the honor and good name of a person which can result in a person's sense of dignity, shame, or humiliation. Someone proven guilty of disseminating electronic information containing defamation as referred to in the elements of Article 27 paragraph (3) of Law number 19 of 2016 concerning amendments to Law number 11 of 2008 concerning Information and Electronic TransactionsÂ This type of research used in this study is a type of empirical legal research, which is a legal research method that uses empirical facts taken from human behavior, with a qualitative approach.The results of the research showed that the perpetrators' violation was a violation of the provisions of Article 27 paragraph (3) of Law number 19 of 2016 concerning amendments to Law number 11 of 2008 concerning Information and Electronic Transactions to be charged with Article 45 Paragraph (1) of the ITE Law which states : Every person who fulfills the elements referred to in Article 27 paragraph (1), paragraph (2), paragraph (3), or paragraph (4) shall be sentenced to a maximum imprisonment of 4 (six) years and / or a maximum fine of Rp 650,000 .000.00 (Six Hundred Fifty Million Rupiah).